2014
DOI: 10.3945/jn.114.191072
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Protein Intake Modulates Lipid Metabolism in Healthy Young Men and Women Consuming a High-Fat Hypercaloric Diet

Abstract: The objective of this study was to evaluate the effect of increasing protein intake, at the expense of carbohydrates, on intrahepatic lipids (IHLs), circulating triglycerides (TGs), and body composition in healthy humans consuming a high-fat, hypercaloric diet. A crossover randomized trial with a parallel control group was performed. After a 2-wk run-in period, participants were assigned to either the control diet [n = 10; 27.8 energy percent (en%) fat, 16.9 en% protein, 55.3 en% carbohydrates] for 4 wk or a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
3
28
2
Order By: Relevance
“…Meta-analysis of high protein/weight loss studies has confirmed their preferential efficacy on the reduction of triglycerides in particular [40]. In the case of a hypercaloric diet, increased protein intake is linked to a trend (i.e., p = 0.07) towards reduced triglycerides [7]. In our study under conditions of weight balance and isocaloric dietary intake, we found no improvements in any of the lipid panels (Table 4).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Meta-analysis of high protein/weight loss studies has confirmed their preferential efficacy on the reduction of triglycerides in particular [40]. In the case of a hypercaloric diet, increased protein intake is linked to a trend (i.e., p = 0.07) towards reduced triglycerides [7]. In our study under conditions of weight balance and isocaloric dietary intake, we found no improvements in any of the lipid panels (Table 4).…”
Section: Discussionsupporting
confidence: 45%
“…Given that skeletal muscle is the largest organ and responsible for the majority of post-prandial glucose disposal [5], an increase in protein intake may promote the preservation of skeletal muscle and lead to improvements in insulin sensitivity [6]. Studies have also shown that increased protein intake may have favorable effects on circulating triglyceride concentrations [7]. Indeed, elevations in protein intake have been linked to many improvements in what many consider the hallmarks of metabolic syndrome (i.e., hypertension, atherosclerosis, hyperlipidemia) [8].…”
Section: Introductionmentioning
confidence: 99%
“…(15) and in vivo observations reporting that high-proteinlow-carbohydrate diets stimulated lipogenic gene expression (FAS and SREBP1) and enzyme activity (FAS, G6PDH, and ME) compared with low-protein-high-carbohydrate diets in rainbow trout and blackspot seabream, respectively (23,75). However, these results are different from the demonstrations in rodents, chickens, or humans reporting that high-protein (HP) diets induce downregulations of fatty acid biosynthesis in liver at both gene expression and enzymatic levels (1,2,7,56,64,67,87,90). Data from mice have shown that an increased flux of AAs reaching the hepatoportal area in HP diet conditions promotes AA catabolism and acetyl-CoA synthesis; however, it was suggested that the synthesized acetyl-CoA is either channeled into the TCA cycle or used for ␤-hydroxybutyrate production, but not converted to fatty acids through unknown reasons (64,72,92).…”
Section: Hepatic Fatty Acid Biosynthesis Was More Responsive To Dietacontrasting
confidence: 55%
“…However, these results are different from the demonstrations in rodents, chickens, or humans reporting that high-protein (HP) diets induce downregulations of fatty acid biosynthesis in liver at both gene expression and enzymatic levels (1,2,7,56,64,67,87,90). Data from mice have shown that an increased flux of AAs reaching the hepatoportal area in HP diet conditions promotes AA catabolism and acetyl-CoA synthesis; however, it was suggested that the synthesized acetyl-CoA is either channeled into the TCA cycle or used for ␤-hydroxybutyrate production, but not converted to fatty acids through unknown reasons (64,72,92). Therefore, DNL rates might be lower or even absent after an HP diet (72).…”
Section: Hepatic Fatty Acid Biosynthesis Was More Responsive To Dietacontrasting
confidence: 52%
See 1 more Smart Citation